MANAGEMENT OF THE ACTIVITIES OF INSTRUCTORS-METHODISTS AND TRAINERS IN A SPORT ORGANIZATION AS A SOCIAL AND PROFESSIONAL PROBLEM - E. Selivanova; A. Nikitin; E. Orshanskaya (Вестник Северо-Кавказского федерального университета)
The article defines the basics of theorizing the process of managing the activity of instructors-methodologists and coaches in a sports organization. The quality of theorization of the identified problems is determined in the structure of clarifying the definitions of the concept of «management of the activity of instructors-methodologists and coaches in a sports organization», «models of management of the activities of instructors-methodologists and coaches in a sports organization», «management technology of the activities of instructors and trainers in a sports organization», «principles of managing the activities of instructors and trainers in a sports organization», «functions of managing the activities of instructors and trainers in a sports organization», «pedagogical conditions for ensuring the proper quality of the results of managing the activities of instructors and trainers in a sports organization». The basics of clarifying theorized models and modeling the conditions for ensuring the proper quality of the results of managing the activities of instructors-methodologists and coaches in a sports organization are revealed.